Fear of COVID-19, risk perception and preventive behavior in health workers: a cross-sectional analysis in middle-income Latin American countries - Bonilla-Asalde, César Antonio (2023)
The aim of this study was to examine the association between fear of COVID-19 and risk perception with preventive behavior in health professionals from four Latin American countries. An analytical cross-sectional study was conducted. Health professionals with on-site care in Colombia, Ecuador, Guatemala, and Peru were surveyed. Information was collected through an online self-report questionnaire. The main variables were preventive behavior as the dependent variable and fear of COVID-19 and risk perception as independent variables. Linear regression was used, and unstandardized beta coefficient and value of ps were calculated. Four hundred and thirty-five health professionals were included, the majority were aged 42 years or older (45.29, 95%CI: 40.65–50.01) and female (67.82, 95%CI: 63.27–72.05). It was shown that the greater the fear of COVID-19, the greater the preventive behavior of COVID-19 infection (B  = 2.21, p  = 0.002 for total behavior; B = 1.12, p = 0.037 for additional protection at work; B = 1.11, p